Pertimbangan Hakim dalam Menjatuhkan Sanksi Pidana terhadap Anak Pelaku Tindak Pidana Pembunuhan Berencana Di Hubungkan dengan Asas Keadilan - Chintia Ella Riska; Chepi Ali Firman Z (UNISBA Press, 2023)
ABSTRACT- The legal problems of crimes committed by children or known as juvenile delinquency, one of which is the crime of premeditated murder in Decision Number: 12/Pid.Sus-Anak/2022/PN. Mkd. The purpose of the research was to find out the judge's considerations in imposing a sentencing decision Number: 12/Pid.Sus-Anak/2022/PN. Mkd in the case of the crime of premeditated murder and the reason the judge did not impose maximum criminal sanctions on the child who committed the crime of premeditated murder in Decision Number: 12/Pid.Sus-Anak/2022/PN. Mkd as a form of criminal responsibility. This research uses normative juridical and empirical juridical approaches. The types of data used are primary data and secondary data. The results of the study show that the judge's considerations in imposing a sentencing decision are Number: 12/Pid.Sus-Anak/2022/PN. Mkd in the case of premeditated murder are the prosecutor's indictment, the purpose of the punishment, the mitigating and aggravating circumstances, the panel of judges tends not to impose the maximum sentence, the hope that the perpetrator will not repeat his actions, the motive for the crime, the attitude of the perpetrator after committing the crime, the consequences . The judge did not impose maximum criminal sanctions on the child who committed the crime of premeditated murder in Decision Number: 12/Pid.Sus-Anak/2022/PN. Mkd. The aim of punishment is oriented towards prioritizing the best interests of the child integrated into the system and model of juvenile justice, encouraging its integration into positive legal norms and child law enforcement, if a child is only sentenced to 8 (eight) years in prison it is feared that the child will not realize his mistake increased insight into criminal acts The purpose of punishment is not to punish, but to improve conditions, care for and protect children as well as the application of theories related to the basic considerations of judges in deciding cases in court hearings namely legal certainty, expediency and legal justice. ABSTRAK- Problematika hukum tindak pidana yang dilakukan oleh anak atau dikenal dengan juvenile delinquency salah satunya tindak pidana pembunuhan berencana dalam Putusan Nomor: 12/Pid.Sus-Anak/2022/PN. Mkd. Tujuan Penelitian dilakukan adalah untuk mengetahui pertimbangan hakim dalam menjatuhkan putusan pemidanaan Nomor: 12/Pid.Sus-Anak/2022/PN. Mkd dalam kasus tindak pidana pembunuhan berencana dan alasan hakim tidak menjatuhkan sanksi pidana maksimum terhadap anak pelaku tindak pidana pembunuhan berencana dalam Putusan Nomor: 12/Pid.Sus-Anak/2022/PN. Mkd sebagai bentuk pertanggungjawaban pidana. Penelitian ini menggunakan pendekatan secara yuridis normatif dan yuridis empiris. Jenis data yang digunakan adalah data primer dan data sekunder. Hasil penelitian menunjukkan bahwa Pertimbangan hakim dalam menjatuhkan putusan pemidanaan Nomor: 12/Pid.Sus-Anak/2022/PN. Mkd dalam kasus tindak pidana pembunuhan berencana adalah dakwaan Jaksa, tujuan pemidanaan, hal-hal yang meringankan dan memberatkan, majelis hakim cenderung tidak menjatuhkan pidana maksimum, harapan pelaku tidak mengulangi perbuatannya, motif tindak pidana, sikap pelaku setelah melakukan tindak pidana, akibat yang ditimbulkan. Hakim tidak menjatuhkan sanksi pidana maksimum terhadap anak pelaku tindak pidana pembunuhan berencana dalam Putusan Nomor: 12/Pid.Sus-Anak/2022/PN. Mkd. Tujuan pemidanaan berorientasi mengutamakan kepentingan terbaik anak terintegrasi ke dalam sistem dan model peradilan pidana anak, mendorong terintegrasinya ke dalam norma hukum positif dan penegakkan hukum anak, jika anak hanya di hukum 8 (delapan) tahun penjara dikhawatirkan bukannya anak tersebut menyadari kesalahannya melainkan anak tersebut dapat betambah wawasannya men genai perbuatan kriminal Tujuan pemidanaan bukanlah pada penghukuman, tetapi perbaikan kondisi, pemeliharaan dan perlindungan anak serta aplikasi teori-teori yang berkaitan dengan dasar pertimbangan hakim dalam memutus perkara dalam sidang pengadilan yakni kepastian hukum, kemanfaatan dan keadilan hukum.